Konsumsi Makan dan Pertumbuhan Larva Helicoverpa armigera Toleran terhadap Pemaparan Helicoverpa armigera Nuclear Polyhedrosis Virus (HaNPV) - Yayan Sanjaya; Wardono Noloperbowo; Tjandra Anggraeni (Jurnal Matematika & Sains, 2004)
An investigation on the effect of repeated infection of Helicoverpa armigera Nuclear Polyhedrosis Virus (HaNPV) to Helicoverpa armigera to know its effect on Helicoverpa armigera tolerance had been carried out. On treatment with 800 (Polyhedral Inclusion Body/dose) PIB/dose indicated that the exposure of HaNPV to H. armigera larva showed no difference significantly (P> 0.05) on its LD50 to every generation exposed. In contrast, H. armigera which had been exposed by HaNPV had a higher food consumption and larval growth rate compared to H. armigera without treatment. This investigation also showed that the increasing food consumption and larvae growth rate of H. armigera was in line with the increase of HaNPV exposure. Infection of HaNPV caused a development of tolerance mechanism in H. armigera.